Power and moral thinking. (June 2020) - Fleischmann, Alexandra; Lammers, Joris
Graphical abstract: Power affects moral judgment through three out of four moral thinking styles. Highlights: Power has complex influences on moral thinking and moral decisions. Power increases three out of four moral thinking styles. Effects of power on morality may be larger than apparent by behavior. Abstract : This review synthesizes research on how feelings of power affect the processing of moral information. Although power is typically viewed as a potentially corruptive force that reduces our morality, we propose that power amplifies moral thinking — but does so in different ways that potentially run in opposite directions. Building on the Moral Orientation Scale framework [1 ], we propose that power increases the tendency to deliberate about moral questions, increases the tendency to integrate feelings and cognitions, and increases the adherence to principles and rules. Feelings of power do not corrupt, but lead to a more rich, mature, and multifaceted form of morality.